PENGARUH PEMBERIAN PENDIDIKAN KESEHATAN PERTOLONGAN PERTAMA PADA KECELAKAAN (P3K) TERHADAP PENGETAHUAN AWAK KAPAL PENUMPANG DI PELABUHAN LAUT MANADO - Kristin Dareda; Agust A. Laya (FKIP, Universitas Palangka Raya, 2021)
Knowledge of first aid (P3K) is very important in caring for yourself and colleagues in an emergency situation that threatens health. Companies are required to provide first aid to provide first aid as quickly as possible whenever a work accident occurs which results in injury to workers. This study aims to see whether there is an effect of first aid health education on the knowledge of passenger ship crew.This study used a quantitative research design using the post-test method with a control group. Respondents in this study were crew of passenger ships at Manado Seaport. The sampling technique used was purposive sampling. Data analysis showed that there were significant differences in crew members' knowledge before and after the first aid intervention. The results of this study indicate that first aid in accidents has a significant effect on the crew's knowledge. However, there are still deficiencies in the implementation of the duties of first aid workers and poor monitoring. First aid facilities and infrastructure in the workplace need to be improved. This study recommends an increase in first aid training and cooperation between all elements of the company.